Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) Pada Materi Laju Reaksi - Cinthree Fauzana Yanti; Suryelita Suryelita (Universitas Negeri Padang, 2021)
Reaction rate material is facts, concepts, calculations and practicum. Learning requires teaching materials to help students find their own concepts starting with contextual problems, one of which is PBL-based LKPD, because it can help students understand concepts through problems so that students are required to think more actively. The research aims at producing alternative teaching materials (helping active students in understanding the material) and determining the validity category. The type of research is R and D with a 4-D model, define, design, develop, and disseminate (not done). The study was limited to the validity test with the research instrument, namely the validity questionnaire. The data collection technique was carried out by distributing questionnaires. The research data by five expert validators were analysed using the Cohen kappa formula. Based on the analysis, the resulting LKPD with a very high validity category is 0,83.